Optoelectronics - Haidar Shahine, Mike (IntechOpen, 2021)
This book represents a unique collection of the latest developments in the rapidly developing world of optoelectronics. The contributing authors to this book are a group of internationally distinguished researchers. This book consists of a collection of chapters divided into two sections, with the first section covering new applications and the second section covering materials and crystal structures topics to support future generations of optoelectronic devices and open the door for future, more demanding applications. This collection of chapters will be of considerable interest to scientists, engineers, physicists, and technologists working in research and development in the fields of optoelectronics and photonics, as well as to young researchers who are at the beginning of their career.